Rhetoric and History in Service of Education in Poland on the Basis of the Script of Rhetoric Lectures at the Jesuit College in Poznań from 1679 - Nowicki, Michał (Biuletyn Historii Wychowania, 2018)
Rhetoric was the most important subject of the Old Polish educational system, with its roots tracing back to the tradition of the Ancient Rome. The statement itself is crucial, due to the fact of the orator’s moral and patriotic duties. Therefore, the lectures were focused not only on the technical aspects of rhetoric, but also on morality, religion and political knowledge. The article consists of two main sections. The first section is dedicated to describing the role of the rhetorical education, as well as, the evolution of the relation between rhetoric and history, which had existed from the 1st century A.D. until the first decades of the 18th century, when history began to separate from rhetoric. The second section is dedicated to presenting the history education in practice, on the example of the Jesuit college in Poznań. The analysis of the matter is based on the script of rhetoric lectures given in Poznań in 1679. With regard to the aforementioned manuscript, one could say, that the most important task of history education, was the patriotic and civil upbringing of pupils, so that they could participate in political and cultural activities. History taught at the College in Poznań was mainly dedicated to Poland, and was of practical nature.